Letter (copy) : Relief for Spain - Tewson, Vincent
010-0073-001 HVT/HTT/HT/125 Secretary's October 20, 1936 Mr. Ronald Stewart, Spanish People's Front, 3, Victoria Street, London, S.W.1 Dear Sir, RELIEF FOR SPAIN Before putting before our General Council your letter of the 17th instant, I should be glad to have fuller information concerning the composition and purposes of the "Co-ordinating Committee for Spanish Relief" which you are forming. As you are perhaps aware the activities of the organised Labour movement in collecting funds for the relief of distress in Spain are being carried on in conjunction with the International Federation of Trade Unions and the Labour and Socialist International. It is not quite clear to me what functions of co-ordination your Committee is intended to serve. Perhaps you can find time to arrange an appointment here when we can discuss with you and your colleague the project you have in view. Yours faithfully, Assistant Secretary. 292/946/10/78